Update on pediatric oral healthcare. Issue 8 (August 2016) - Rizzolo, Denise; Bowser, Jonathan
Abstract : ABSTRACT: As part of the patient-centered medical home, clinicians are being asked to apply fluoride varnish and perform oral examinations in children. This article reviews the latest national recommendations for fluoride varnish use to prevent dental caries.